2019
DOI: 10.1111/ctr.13615
|View full text |Cite
|
Sign up to set email alerts
|

Renal outcome after simultaneous heart and kidney transplantation

Abstract: Simultaneous heart‐kidney transplant (HKTx) is a valid treatment for patients with coexisting heart and renal failure. The aim of this study was to assess renal outcome in HKTx and to identify predictive factors for renal loss. A retrospective study was conducted among 73 HKTx recipients: Donors’ and recipients' records were reviewed to evaluate patients’ and renal transplants’ survival and their prognostic factors. The mean follow‐up was 5.36 years. Renal primary non‐function occurred in 2.7%, and complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
2
13
0
2
Order By: Relevance
“…Previous studies of patients receiving HKTx reported considerably impaired renal graft and patient survival after the first year of transplantation. After five years, patient survival was reported between 53 to 80% versus 84 to 86% in case of solitary KTx, whereas differences in renal graft survival were slightly less pronounced (69% versus 76%) [1,[4][5][6][7]. Our study demonstrates similar results after one and five years, however; significant differences in graft and patient survival diminished over time, which is mainly explained by a lower rate of DWFG following the first year after HKTx.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Previous studies of patients receiving HKTx reported considerably impaired renal graft and patient survival after the first year of transplantation. After five years, patient survival was reported between 53 to 80% versus 84 to 86% in case of solitary KTx, whereas differences in renal graft survival were slightly less pronounced (69% versus 76%) [1,[4][5][6][7]. Our study demonstrates similar results after one and five years, however; significant differences in graft and patient survival diminished over time, which is mainly explained by a lower rate of DWFG following the first year after HKTx.…”
Section: Discussionsupporting
confidence: 64%
“…In our study we therefore investigated the outcome of patients undergoing HKTx in comparison to patients undergoing solitary KTx, focusing on renal graft performance and survival. Previous investigations on the matter demonstrated that graft damage due to the necessity of complex and prolonged ICU treatment as well as early renal graft loss due to increased in-hospital mortality following HKTx are major limitations for the success of this combined approach [1,5,6,14]. Significantly lengthened ICU treatment, frequent necessity of subsequent dialysis and a considerable rate of primary nonfunction (18.5%; 5 of 27 patients) and in-hospital mortality (22%, 6 of 27 patients) in our patients undergoing HKTx corroborate these previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…До настоящего времени не существует каких-либо рекомендаций, в каких случаях надо использовать одномоментную или поэтапную методику. Несмотря на увеличение срока холодовой ишемии для почечного трансплантата, многие авторы выступают в пользу двух последовательных операций [64,66]. В этом случае наличие восстановительного периода для нового трансплантированного сердца позволяет оптимизировать статус гидратации перед пересадкой почки и уменьшить негативное влияние на почечный трансплантат таких факторов, как низкое перфузионное давление и нестабильные гемодинамические условия.…”
Section: трансплантация почки реципиентам сердцаunclassified